Evaluation and comparative analysis on reduction of Globalfiler™ reaction volume in low template samples. (December 2017) - Brito, P.; Gouveia, N.; Bogas, V.; Bento, A.M.; Balsa, F.; Lopes, V.; Sampaio, L.; Cunha, P.; Bento, M.São; Serra, A.; Porto, M.J.
Abstract: In forensic genetic laboratories, low template DNA (LTDNA) samples can be a challenge in the attempting to obtain genetic profiles with the most information possible. In this study, volume reduction on amplification reaction was tested in the kit Globalfiler™, with the intend to optimize the results in LTDNA samples. To carry out this study, several samples extracted with PrepFiler ® were diluted successively to very low concentration values. All samples and respective dilutions were amplified with Globalfiler™, for both reaction volumes of 12, 5 μL and 25 μL. Capillary electrophoresis was performed on the ABI PRISM ® 3500 Genetic Analyzer and the HID files generated were analysed using GeneMapper ® ID-X v.1.4. Forensic DNA samples with very low values of DNA concentration were also tested in the same conditions. The results indicate that the reduction of volume in amplification reaction with Globalfiler™ can often produce higher quality profiles, resulting as an alternative to enhance allelic recovery.